2023
DOI: 10.1093/inthealth/ihad013
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with COVID-19 vaccine hesitancy among healthcare workers in Cameroon and Nigeria: a web-based cross-sectional study

Abstract: Background This study investigated the determinants of coronavirus disease 2019 (COVID-19) vaccine hesitancy among healthcare workers (HCWs) in Cameroon and Nigeria. Methods This analytic cross-sectional study was conducted from May to June 2021, including consenting HCWs aged ≥18 y identified using snowball sampling. Vaccine hesitancy was defined as indecisiveness or unwillingness to receive the COVID-19 vaccine. Multilevel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…In contrast, the following factors were associated with VH, gender [ 50 , 55 , 85 , 86 , 89 , 94 ], age [ 50 , 53 , 58 , 64 , 73 , 86 , 94 ], ethnicity [ 64 ], education level [ 50 , 55 , 70 , 85 ], religion [ 71 ], marital status [ 58 ], presence of chronic illness [ 62 ], cadre [ 50 , 58 , 64 , 71 , 84 , 93 ], and income level [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the following factors were associated with VH, gender [ 50 , 55 , 85 , 86 , 89 , 94 ], age [ 50 , 53 , 58 , 64 , 73 , 86 , 94 ], ethnicity [ 64 ], education level [ 50 , 55 , 70 , 85 ], religion [ 71 ], marital status [ 58 ], presence of chronic illness [ 62 ], cadre [ 50 , 58 , 64 , 71 , 84 , 93 ], and income level [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the effectiveness of many strategies that have been put in place to facilitate the distribution of the vaccines in Africa [ 7 ], an unpredicted resistance of the population to get vaccinated has been noticed [ 4 , 13 ]. As documented by other studies, many theories could explain this controversy, and factual evidence has pointed to poor information or misinformation as the major factors that spark fears of potential side effects of the vaccines [ 6 , 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even if some studies have reported misinformation, mistrust of vaccine safety and effectiveness, and religion as just some of the factors associated with COVID-19 hesitancy, vaccine hesitancy is a context-dependent phenomenon that should be examined and monitored regarding local reality [ 4 , 12 , 13 ]. Previous studies have reported that in Cameroon, the lack of confidence in approved vaccines as well as concerns about vaccine side effects were associated with vaccine hesitancy amongst health personnel [ 6 , 14 ]. Still, no community-based study, to the best of our knowledge, has investigated the reason for COVID-19 vaccine refusal in Cameroon in general.…”
Section: Introductionmentioning
confidence: 99%
“…In Chad, 21% of participants in a survey reported lacking trust in the government as a factor related to their refusal to vaccinate [76]. Another study among healthcare workers in Cameroon and Nigeria based on a web-based cross-sectional study also determined mistrust in the pharmaceutical industries, the government, and public health regulatory authorities in uenced their decision to refuse vaccination [77].…”
Section: Discussionmentioning
confidence: 99%